If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -3(5 + -3x) = 0 13x + (5 * -3 + -3x * -3) = 0 13x + (-15 + 9x) = 0 Reorder the terms: -15 + 13x + 9x = 0 Combine like terms: 13x + 9x = 22x -15 + 22x = 0 Solving -15 + 22x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 22x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 22x = 0 + 15 22x = 0 + 15 Combine like terms: 0 + 15 = 15 22x = 15 Divide each side by '22'. x = 0.6818181818 Simplifying x = 0.6818181818
| x+(2x+1)+(3x+2)=170 | | 1.1X+2.2=9.9 | | 2x+4(x-3)=3x-15 | | 1.2=ln(x/x-750) | | 18x^2+18x=0 | | 0.7X+1.5=3.88 | | 3x(2x^5y^3z^3)/9x^2 | | -2x-1=2x+23 | | (3x-2)(x-4)=6x-4 | | -m-1=2m+5 | | 9/15*4/4= | | 42x^2+36x=0 | | 7/10*180 | | 2t^2-50=0 | | 4t^3-8t^2-140t= | | R^6-64= | | X^3+2=3x^2+4x | | 12x^6-8x^5-145x^4-95x^3+140x^2-16= | | x+3=-2x+21 | | -16t^2+64t+880= | | 2p+6=4p+-10 | | 12y^2-3=-16y | | 7/11 | | 3/11*7/9 | | 3/11*7-9 | | 100[0.07(n+6)]= | | 4(z-5)=-8(z+6) | | Y*y^7= | | 20x+9=5x+3(5x+3) | | 9-v=4v+8 | | 8x+8=2x | | 1.6/2=x/9 |